Features of typology and design of entertaining establishments - Абизов, В. А.; Вовкотруб, О. М. (Art and Design, 2018)
Identification of features of classifications and system-structural principles of the typology of the entertaining institutions' architectural environment. Consideration of design features of objects of leisure according to the hierarchical levels of formation and development of their environment. The research is based on a systematic approach that allows us to consider the architectural environment of entertaining institutions as hierarchically subordinate to the integrity. Also are used methods of historical, comparative and typological analysis, field surveys. The article generalizes features of the typology of entertaining institutions. The specifics of their location in cities and rural settlements are considered. The classification of entertaining establishments for placing in buildings is offered. The hierarchical levels of formation and development of the architectural environment design of leisure facilities are revealed. Features and examples of design solutions are considered, including the existing buildings and structures, taking into account the transformation and adaptation of them for entertaining establishments. The typology of entertainment establishments is explored and systematized, their classification for placement in buildings is proposed. The peculiarities of the entertaining establishments design in accordance with the revealed hierarchical levels of formation and development of the architectural environment of leisure facilities are presented. The revealed features of the typology and approaches of the design of entertaining facilities can be used in the practical activities of designers and leisure organizations, which will allow them to introduce creative ideas and tools for creating a harmonious environment during their design.